PENINGKATAN KEMAMPUAN GURU SEKOLAH DASAR MELALUI DISKUSI KELOMPOK KERJA GURU DALAM MEMANFAATKAN LINGKUNGAN SEKOLAH SEBAGAI SUMBER BELAJAR - Suterisno Suterisno (UNIVERSITAS BENGKULU, 2017)
Many teachers are very rare and never even use the school environment as a source of learning. This study was designed in the form of a School Action Research which consists of two cycles. The subjects of this study are teachers of SDN 03 in Gugus14 District Kabawetan Kepahiang Regency. From the results of the research implementation obtained the following data: In the first cycle the average attitude of teachers discuss discussion is 70.4 up in the second cycle to 78.8, the average value of learning scenarios in the first cycle is 67.8 up on cycle II to 80, the average value of the implementation of learning in the first cycle that is 71.84 up on the second cycle to 80.8. This means that coaching and guidance through teacher work group discussion approach can improve teachers' ability in utilizing school environment as a learning resource.